Трансформації польської демократії періоду ХХ – початку ХХІ століття - Марчук, М. І.; Marchuk, M. I.; Марчук Микола Іванович (Аналітично-порівняльне правознавство. - 2021. - № 2. - С. 5-10, 2021)
Досліджено та науково осмислено процес становлення та еволюції Польщі як сучасної демократичної європейської держави. Вказано на значимість впливу демократичних традицій польського народу на формування чинної моделі державного ладу Республіки Польща. Встановлено загальні хронологічні рамки кожного із періодів демократизації польського суспільства, починаючи з часів «шляхетської демократії». Визначено основні характеристики стадій демократичного розвитку Польщі аж до періоду сучасності. З’ясовано основні чинники, що вплинули на перебіг демократичного транзиту у Польській державі.

The article is devoted to the study and scientific understanding of the process of formation and evolution of Poland as a modern democratic European state. The importance of the influence of the democratic traditions of the Polish people on the formation of the current model of the state system of the Republic of Poland is pointed out. The general chronological framework of each of the periods of democratization of Polish society, starting from the times of «noble democracy», has been established. The main characteristics of the stages of democratic development of Poland up to the present period are determined. The main factors that influenced the course of democratic transit in the Polish state have been clarified. It turns out that the peculiarities of modern Polish statehood are due to the historical traditions of Polish democracy, the mentality of the Polish people, membership in the EU and other in-ternational organizations. It is emphasized that the implementation of economic and institutional transformations in the Polish state in the post-Soviet period was accompanied by the simultaneous formation of civil society. It is established that the result of democratic transit in the Republic of Poland is a liberal democracy of the western type with a certain bias towards social democracy. Emphasis is placed on the decisive role of European integration processes in the establishment of the Republic of Poland as a democratic, legal and social state. Based on the analysis of current legislation and ongoing reforms in the law-making sphere, the main factors that determine the existing systemic threats to the rule of law and democracy in Poland at the present stage of its state-building have been identified. It is stated that Polish democracy at present shows some negative tendencies, but it is unlikely to collapse due to the current challenges, as the Republic still maintains a balance between state power and political freedom of citizens and their associations and the general atmosphere in Polish society remains open and free.

Исследован и научно осмыслен процесс становления и эволюции Польши как современного демократического европейского государства. Указано на значимость влияния демократических традиций польского народа на формирование действующей модели государственного строя Польши. Установлены общие хронологические рамки каждого из периодов демократизации польского общества, начиная со времен «шляхетской демократии». Определены основные характеристики стадий демократического развития Польши вплоть до XXI века. Выяснены основные факторы, повлиявшие на ход демократического транзита в Польском государстве.
Transformations of Polish democracy in the period of the XX - beginning of the XXI century
Keywords: Держава і право. State and Law. Государство и право; Наукові публікації. Scientific publications. Научные публикации; Історія. History. История; Конституційне право. Constitutional Law. Конституционное право; історико-правовий аналіз; historical and legal analysis; историко-правовой анализ; демократія; democracy; демократия; зарубіжний досвід; foreign experience; зарубежный опыт; Польща; Poland; Польша; громадянське суспільство; civil society; гражданское общество; ринкова економіка; market economy; рыночная экономика; вільна преса; free press; свободная пресса; соціалізм; socialism; социализм